Transformation of Information Technology-Based Islamic Religious Education Learning Media in Enhancing Learning Quality in Secondary Schools - Sartina Sartina; Sri Wahyuni Pohan; Mhd. Fikri Ulinnuha; Muslimin Muslimin (Integrasi: Jurnal Studi Islam dan Humaniora, 2026)
This study aims to analyze the transformation of information technology-based learning media in Islamic Religious Education (IRE) to enhance learning quality in secondary schools. The research employs a qualitative approach using literature review methods and limited observation of technology-based learning practices. The findings indicate that the transformation of IT-based learning media, such as digital applications, interactive multimedia, and online learning platforms, significantly improves student engagement, learning effectiveness, and deeper understanding of subject matter. Furthermore, the use of technology-based media promotes more flexible and adaptive instructional innovation in response to modern educational demands. However, several challenges remain, including limited infrastructure, teachers’ digital competence, and unequal access to technology. Therefore, policy support, teacher training, and adequate facilities are essential to optimize the use of technology in Islamic education